Ephedra extract-mediated gold nanoparticles on Kaolin: A natural approach for reduction and stabilization, with evaluation of antioxidant and anti-ovarian cancer activities - Hui Yang; Cui Wang; Qingjiang Wang; Feng Han (Journal of Science: Advanced Materials and Devices)
A straightforward, efficient, and environmentally friendly method has been developed to synthesize gold nanoparticles (Au NPs) supported on kaolin with no harmful additives, ephedra flower extract acts as a biogenic stabilizing and reducing agent. An analysis of the Au NPs/Kaolin composite's structural properties was conducted using FE-SEM, TEM, EDX, and XRD assays. The biological activity of the composite was evaluated through cytotoxicity tests using the MTT assay. In addition, its potential anti-ovarian cancer properties were tested against several ovarian cancer cell lines, including TOV-21G, OV-90, SW 626, and UWB1.289, with IC50 values found to be 112, 250, 278, and 243 μg/mL, respectively. The ovarian cancer cell lines showed a dose-dependent decline in % cell viability. The HUVEC cell line was also used to evaluate the material's biocompatibility with normal cells. Based on the results, the bio-composite material is found promising as a therapeutic agent for treating human ovarian cancer.